Why Do We Wear What We Wear?: Female Schoolteachers’ Activism Against Hegemonic Saree-Only Dress Policy in Sri Lanka - Jayasooriya, Lasni Buddhibhashika (Indonesian Journal of Social Research (IJSR), 2024)
The longstanding expectation for female schoolteachers in Sri Lanka to wear sarees is primarily influenced by cultural norms and religious traditions. In November 2022, an organized movement of female activists began opposing this social imperative by wearing casual attires at school, making it the first organized movement of its kind. This paper analyses the island-wide protest led by female schoolteachers as a case through a case study interview with one of the leaders of the activist movement. A document analysis is utilized to examine the background of the saree-only policy. By doing so, a broader understanding of the movement against the saree-only policy and its impetus were gained focusing on how it influenced teacher identity development. The paper offers a critical overview of the control exerted over female schoolteachers, shaped by cultural, religious, and political influences, and how the movement in 2022 reimagined their identities through changes in attire. Findings indicate that female teacher activism challenges longstanding traditions and calls for a redefinition of "Sri Lankan female teacher" exercising individual and collective agency against cultural and religious hegemony despite resistance to change at many levels.